2004
DOI: 10.1165/rcmb.2002-0110oc
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin and Neurotrophin Receptor Protein Expression in the Human Lung

Abstract: Neurotrophins (NTs) promote survival and differentiation of central and peripheral neurons, and display several activities also in non-neuronal cells. Human lungs synthesize and release NTs, which are probably involved in the pathophysiology of pulmonary disturbances. In this article the expression and anatomic localization of nerve growth factor, brain-derived neurotrophic factor, and NT-3 and of corresponding high-affinity receptors TrkA, TrkB (full-length and truncated [TR-] isoforms), TrkC, and of the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
115
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 33 publications
(55 reference statements)
12
115
2
5
Order By: Relevance
“…The data described above confirmed our previous experimental findings (8)(9)(10)(11), hence improving our knowledge on the role of the neurotrophins in the regulation of the meningeal microenvironment and their direct participation in the neoplastic transformation and cellular survival, both essential aspects of the malignant development.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The data described above confirmed our previous experimental findings (8)(9)(10)(11), hence improving our knowledge on the role of the neurotrophins in the regulation of the meningeal microenvironment and their direct participation in the neoplastic transformation and cellular survival, both essential aspects of the malignant development.…”
Section: Discussionsupporting
confidence: 87%
“…A definite role of NTs in the dural and leptomeningeal compartments is not well ascertained but a previous study on the expression of mRNAs for NTs revealed high levels of NT3 and NGF in the normal rat dura mater (7). Our observations on the localization and possible roles in different non-neuronal tissues such as lymphoid, lung and prostate (8)(9)(10)(11) encouraged us to persist in our experimental investigations in order to find a possible involvement of NTs in dura mater, both in physiological and pathological conditions (meningiomas).…”
Section: Introductionmentioning
confidence: 80%
“…Local inhibition of the TrkA receptor and consecutive blocking of NGF signaling may either directly lead to the apoptosis of pulmonary PC, or it may act indirectly via other TrkA-expressing inflammatory cells such as T cells (19) and eosinophils (32) and thus prevent the regulation of other extrinsic factors. In support of this, a previous study shows that reduction of NGF levels leads to a significant reduction of IL-4 levels and prevents the development of airway hyperresponsiveness in OVA-sensitized mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of NGF to TrkA induces phosphorylation of an intracellular tyrosine kinase and activation of signaling pathways that, in turn, induce numerous biologic effects (Hempstead et al, 1991;Bothwell, 1995;Barrett, 2000). NGF and its receptors are expressed in neural tumors like neuroblastoma (Nakagawara et al, 1992;Suzuki et al, 1993) and glioma (Eberhart et al, 2001) and also in nonneural tumors like prostate (George et al, 1998), breast (Descamps et al, 2001), lung (Ricci et al, 2004), and pancreatic cancers (Zhu et al, 2002), suggesting that the NGF-TrkA signaling system is frequently involved in cell migration, growth, and survival during cancer progression. Although reports are not consistent, immunohistochemical studies have revealed that TrkA expression is observed mainly in the cytoplasm of pancreatic cancer cells, whereas intense NGF and p75 NGFR expression is observed in the peripheral nerve (Miknyoczki et al, 1999;Zhu et al, 1999;Sakamoto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%